Female Sexual Dysfunction: A Case Study of Disease Mongering and Activist Resistance - Tiefer, Leonore (PLoS Medicine, 2006)
"Tiefer highlights key steps in the ""creation"" of a new diagnosis, female sexual dysfunction, and of the campaign to challenge its reductionist approach to women's sexual problems. "
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; corps; cours; discipline; discours dominant; inégalités; patriarcat; postmodernisme; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; états-unis

La santé est politique - Vuille, Marilène; Rey, Séverine; Fussinger, Catherine; Cresson, Geneviève (Nouvelles Questions Feministes, 2006)
Keywords: 1900-1909; 1900-1999; 1970-1979; 1980-1989; 1990-1999; allemagne; approches et analyses; care; corps; cours; discipline; europe; france; inégalités; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; sciences humaines; soc2051; sociologie; suisse; systèmes d'oppressions; thématiques; travail

Unveiled Sentiments: Gendered Islamophobia and Experiences of Veiling among Muslim Girls in a Canadian Islamic School - Zine, Jasmin (Equity & Excellence in Education, 2006)
The practice of veiling has made Muslim women subject to dual oppressions--racism and Islamophobia--in society at large and patriarchal oppression and sexism from within their communities. Based on a narrative analysis of the politics of veiling in schools and society, the voices of young Muslim women attending a Canadian Islamic school speak to the contested notion of gender identity in Islam. The narratives situate their various articulations of Islamic womanhood in ways that both affirm and challenge traditional religious notions. At the same time they also are subject to Orientalist representations of veiled and burqa clad women that represent them as oppressed and backward. Focusing on ethnographic accounts of veiling among Muslims girls who attended a gender-segregated Islamic high school in Toronto, this discussion allows a deeper understanding of how gendered religious identities are constructed in the schooling experiences of these Muslim youth. (Contains 11 notes.)
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; corps; cours; discipline; féminisme islamique; intersectionnalité; islamophobie; ontario; patriarcat; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences de l'éducation; sex2283; sexisme; systèmes d'oppressions; thématiques; toronto; voiles islamiques